The Influence Of Transformational Leadership And Motivation On Work Engagement Of Civil Servants At UIN Alauddin Makassar - Rika Dwi Ayu Parmitasari; Nurmiati Nurmiati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of transformational leadership and motivation on work engagement among civil servants at UIN Alauddin Makassar. Data collection by observation and distribution of questionnaires via Google Form to 155 civil servants. This research used quantitative methods, with the data analysis tool used was Smart-PLS. The results of this research showed that (1) transformational leadership has a positive and significant effect on work motivation, (2) transformational leadership has a positive and significant effect on work engagement, (3). Motivation has a positive and significant effect on the work engagement of civil servants at UIN Alauddin Makassar. These results showed that the transformational leadership style applied by the leaders of UIN Alauddin Makassar operates efficiently and effectively through exemplary methods. This method can increase strength as a component of employee work engagement.